Exploring the Persuasiveness of Accounting Numbers in the Framing of 'Performance' – A Micro-Level Analysis of Performance Review Meetings. Issue 3 (27th May 2018) - Goretzki, Lukas; Mack, Simone; Messner, Martin; Weber, Jürgen
Abstract: Based on a micro-level analysis of performance review meetings and drawing on an interactional framing perspective, this paper analyses the role of accounting numbers as 'framing devices' in discussions about performance. Analyzing interactions between superiors and subordinates, we examine how and why these two groups of actors mobilize different accounting numbers to make claims about performance and try to persuade the other party. Our interest is with the choice of accounting numbers and how they come to be seen as persuasive. The main theoretical argument developed in this paper is that whether a specific accounting number or indicator comes to be seen as persuasive or not in a particular situation is both a matter of how legitimate the underlying indicator is to the actors involved as well as whether they regard the signal it provides, i.e. the actual outcome on this particular indicator, as salient when compared to the actual outcomes on alternative indicators. Taken together, our findings suggest that persuasiveness is not an 'objective' quality of accounting numbers, but a situated achievement that results from interactive alignments between different actors with potentially competing interests.